BATIK REFUGIA SEBAGAI PRODUK UNGGULAN DAN PENDUKUNG DESA WISATA EDUKASI PERTANIAN JATIREJOYOSO - Ratnawati, Nurul; Ruja, I Nyoman; Purnomo, Agus; Rapita, Desinta Dwi; Bashofi, Ferdinan (Universitas Negeri Malang, 2024)
REFUGIA BATIK AS A PRODUCT OF EXCELLENCE AND A SUPPORTER OF THE JATIREJOYOSO VILLAGE OF AGRICULTURAL EDUCATION AND TOURISM Inadequate human resources cause the community to lack independence and self-confidence in managing, running, and developing the “Taman Refugia” agricultural education tourism. The solution to this problem is to develop and train the manufacture of distinctive and superior products that can support tourism activities in the Jatirejoyoso Agricultural Education Tourism Village. The purpose of this development and training activity is to create and create batik that is characteristic of Jatirejoyoso Village, and to train the community to produce the batik. The method of implementing community service in the development and training of the Refugia batik motif is 1) preparation stage, 2) implementation stage, and 3) follow-up stage. The results of the community service activities show that participants can make Refugia batik with assistance. Thus, the results can be used to support the development and facilitation of the Jatirejoyoso agricultural education tourism village. Sumber daya manusia yang tidak memadai menyebabkan masyarakat tidak memiliki kemandirian dan rasa percaya diri dalam mengelola, menjalankan, serta mengembangkan wisata edukasi pertanian “Taman Refugia”. Solusi terhadap permasalahan tersebut yaitu dengan melakukan pengembangan dan pelatihan pembuatan produk khas dan unggulan yang dapat mendukung kegiatan pariwisata di Desa Wisata Edukasi Pertanian Jatirejoyoso. Adapun tujuan dari kegiatan pengembangan dan pelatihan ini yaitu membuat serta menciptakan batik yang menjadi ciri khas Desa Jatirejoyoso, serta melatih masyarakat untuk memproduksi batik tersebut. Metode pelaksanaan pengabdian masyarakat dalam kegiatan pengembangan dan pelatihan motif batik Refugia yakni: 1) tahap persiapan, 2) tahap pelaksanaan, dan 3) tahap tindak lanjut. Hasil kegiatan pengabdian menunjukkan bahwa peserta dapat membuat batik Refugia dengan pendampingan. Sehingga, hasilnya dapat digunakan sebagai penunjang pengembangan dan fasilitasi desa wisata edukasi pertanian Jatirejoyoso.